Clinical predictors for surfactant retreatment in preterm infants with respiratory distress syndrome: the results of a pooled analysis - Carlo Dani; Chiara Poggi; Massimo Agosti; Massimo Bellettato; Pasqua Betta; Paolo Biban; Luigi Corvaglia; Raffaele Falsaperla; Carlo Forcellini; Diego Gazzolo; Eloisa Gitto; Camilla Gizzi; et al. (Italian Journal of Pediatrics)
Abstract Background The issue of retreatment with surfactant of infants with respiratory distress syndrome (RDS) has been poorly investigated. Our aim was to identify possible clinical predictors of the need for multiple doses of surfactant in a large cohort of very preterm infants. Methods Data were analyzed from three previous studies on infants born between 25+ 0 and 31+ 6 weeks of gestation with RDS who were treated with surfactant. Results We studied 448 infants. Among them 306 (68%) were treated with a single dose of surfactant and 142 (32%) were treated with multiple doses. Multivariable mixed effects logistic regression analysis showed that the odd of requiring multiple doses of surfactant was significantly lower in patients with higher gestational age (27–28 vs. 25–26 wks: OR 0.46, 95% C.l. 0.26–0.79; ≥29 vs. 25–26 wks: OR 0.34, 95% C.l. 0.13–0.85; overall P = 0.013), while it increased in infants born to mothers with hypertensive disorders of pregnancy (OR 2.53, 95% C.l. 1.49–4.31; P < 0.001) and with hemodynamically significant PDA (OR 2.74, 95% C.l. 1.66–4.53, P < 0.001). Conclusions Gestational age, hypertension in pregnancy, and hemodynamically significant PDA can predict the need for multiple doses of surfactant. Further investigation is needed to evaluate if these sub-groups of preterm infants represent specific phenotypes of RDS who deserve a peculiar surfactant treatment.